PENGARUH ELECTRONIC COMMERCE TERHADAP DAYA SAING USAHA UMKM - Sulastri, S; Nuryanti, B. Lena; Mulyadi, Hari; Fadhilla, F (Journal of Business Management Education (JBME), 2021)
The purpose of this study was to examine and analyze acquiring customers, optimizing conversions, maximizing website performance, ensuring a positive user experience, retaining customers and use web analytics at the Binong Jati Central Indusry knitting Bandung SMEs. The population in this study is the Binong Jati Central Indusry knitting Bandung with 160 respondents. The method used in this study is an explanatory survey to explore the problem situation. The sampling technique used is nonprobability sampling using path analysis. The results of electronic commerce produce a positive effect on business competitiveness